2018
DOI: 10.1175/bams-d-17-0164.1
|View full text |Cite
|
Sign up to set email alerts
|

The Setup of the MesoVICT Project

Abstract: MesoVICT focuses on the application, capability, and enhancement of spatial verification methods as applied to deterministic and ensemble forecasts of precipitation, wind, and temperature over complex terrain and includes observation uncertainty assessment. THE SETUP OF THE MesoVICT PROJECTManfreD Dorninger, eriC gillelanD, BarBara Casati, Marion P. MitterMaier, elizaBeth e. eBert, BarBara g. Brown, anD laurenCe J. wilson A s numerical weather prediction (NWP) models began to increase considerably in resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 88 publications
0
39
0
Order By: Relevance
“…Importantly, however, most exisiting spatial verification metrics are not well suited to evaluate probabilistic forecasts. Notably, one of the aims of the ongoing community project MesoVICT (Mesoscale Verification Intercomparison over Complex Terrain) is to test the suitability of existing spatial verification methods for ensemble forecasts (Dorninger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, however, most exisiting spatial verification metrics are not well suited to evaluate probabilistic forecasts. Notably, one of the aims of the ongoing community project MesoVICT (Mesoscale Verification Intercomparison over Complex Terrain) is to test the suitability of existing spatial verification methods for ensemble forecasts (Dorninger et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In 2007 a spatial verification method inter-comparison (Gilleland et al 2009(Gilleland et al , 2010 The use of spatial verification methods has therefore become commonplace for atmospheric NWP (see Dorninger et al 2018 and references within). Neighbourhood-based methods in particular have become popular due to the relative ease of computation and intuitive interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…The correctly predicted structure is not rewarded in any way. Following the advent of high-resolution numerical weather predictions, this effect, known as double penalty (Ebert, 2008), has motivated the introduction of numerous new spatial verification tools.…”
Section: Introductionmentioning
confidence: 99%
“…In a comprehensive review of the field, Gilleland et al (2009) identified four main strategies that deal with the double penalty problem and supply useful diagnostic information on the nature and gravity of forecast errors. The classification was updated to include an emerging fifth class in Dorninger et al (2018). Proponents of the first strategy, the so-called neighbourhood approach, attempt to ameliorate the issue via successive application of spatial smoothing filters (Theis et al, 2005;Roberts and Lean, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation